Seismic assessment of masonry cross vaults through numerical nonlinear static and dynamic analysis - Bianchini, Nicoletta (2019)
Masonry vaults represent a pleasant typology of structural horizontal element in traditional architecture and historical buildings, widespread on a large scale along all the European countries, even those characterized by a high level of seismicity. However, they are some of the most vulnerable structural elements particularly under dynamic actions. Therefore, the assessment of their structural safety and the determination of their stress field is a very important task for preservation of historic buildings. Vaults have been studied from an architectural and structural point of view as sequences of arches, and thus extending the use of bidimensional tools of analysis. This assumption can be reliable for the analysis of barrel vaults, but it is not always the most appropriate solution for investigating more complex vaulted systems with a not negligible three-dimensional behavior. The paper presents on the analysis of a particular groin vault, typically found in monumental buildings which will be successively tested during an experimental dynamic campaign on the shake table. Among all the failure mechanisms of this type of vault, the shear failure is one of the most frequently recorded during post-earthquake surveys. The activation of the shear response is caused by asymmetric boundary conditions and difference in stiffness between two sides of the vault, as it occurs in groin vaults covering churches aisles characterized by the presence of a perimeter wall on one side and two columns on the other side. The main aim of the paper is to investigate the seismic response of a brick groin vault simulating the boundary conditions and loadings of an aisle in a three naves church prototype. Static and dynamic nonlinear numerical analyses were performed using a finite element model. The boundary conditions simulate from one side the presence of a perimeter wall and from the other side the two columns between the main and the lateral nave. The role of the infill and